Effects of warming up on balance: implications for primary prevention against posture problems and sports injuries (2002)
It is known that warning up has positive effect on motor or performance skills. We therefore deigned this study to emulate the effect of warming up on control of balance and see the implication on using warming up as primary prevention against postural problems and sport injuries. Sixteen volunteers with records of shortening hamstring muscle took part in the study. The design for the study as one group pre-test-post test experimental design. Measurement of range of motor (ROM) was taken and the assessment of shortening hamstring in balance was carried out using the computerized balance master system (BMS) tests. The mean standard deviation and t-test were used to describe and interpret the results of the study at 0.05 level of significance. Although the study revealed that there was no significant relationship between warming up and control of balance with shortening hamstring muscle, a trend was established showing relationship between warming up and stretching of muscle. Therefore proper warming up exercises should be emphasised before any strenuous motor performance to prevent postural problems and sport injuries.